IMPLEMENTASI THEORY OF REASONED ACTION OLEH AJEN FISHBEIN PADA PENELITIAN SIKAP DAN NORMA SUBJEKTIF TERHADAP MINAT MAHASISWA UNIVERSITAS BATURAJA MENABUNG SAHAM YANG ADA DI BURSA EFEK INDONESIA - Muhamad Mardiansyah; Darman Syafe’i (Ekonomika, 2020)
This research aims to analyze the implementation of the theory of reasonedaction by Ajen Fishbein on attitudes and subyektive norm toward intention to savingstocks. Students College of Baturaja University were taken as the case studi. Bothprimary and secondary data were obtained in this study. Secondary data were obtainedfrom various sources such as journals, books and other related publication. Primary datawere obtained using questionnaires which were distributed to the target respondents. AMultiple Linear Regression Analysis with the SPSS program was employed to analyzedata. The result showed that attitudes and subjective norm had a positive and significanteffect on the intention and subjective norm was found dominant. It suggestted the referentgroup can help provide information, educate and motivate to increase normative beliefsand motivate students to develop intention.